Design and experimental evaluation of network-assisted strategies for HTTP adaptive streaming - G. Cofano; Luca De Cicco; Thomas Zinner; Anh Nguyen-Ngoc; P. Tran-Gia; Saverio Mascolo (Proceedings of the 7th International Conference on Multimedia Systems, 2016)
In this paper we investigate several network-assisted streaming approaches which rely on active cooperation between video streaming applications and the network. We build a Video Control Plane which enforces Video Quality Fairness among concurrent video flows generated by heterogeneous client devices. To the purpose, a max-min fairness optimization problem is solved at run-time. We compare two approaches to actuate the optimal solution in an SDN network: the first one allocating network bandwidth slices to video flows, the second one guiding video players in the video bitrate selection. Performance is assessed through several QoE-related metrics, such as Video Quality Fairness, video quality, and switching frequency. The impact of client-side adaptation algorithms is also investigated.
Keywords: dash; adaptive video streaming; control plane; fairness; network-assistance; quality of experience